11(x+3)=4(3x-4)

Simple and best practice solution for 11(x+3)=4(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(x+3)=4(3x-4) equation:


Simplifying
11(x + 3) = 4(3x + -4)

Reorder the terms:
11(3 + x) = 4(3x + -4)
(3 * 11 + x * 11) = 4(3x + -4)
(33 + 11x) = 4(3x + -4)

Reorder the terms:
33 + 11x = 4(-4 + 3x)
33 + 11x = (-4 * 4 + 3x * 4)
33 + 11x = (-16 + 12x)

Solving
33 + 11x = -16 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
33 + 11x + -12x = -16 + 12x + -12x

Combine like terms: 11x + -12x = -1x
33 + -1x = -16 + 12x + -12x

Combine like terms: 12x + -12x = 0
33 + -1x = -16 + 0
33 + -1x = -16

Add '-33' to each side of the equation.
33 + -33 + -1x = -16 + -33

Combine like terms: 33 + -33 = 0
0 + -1x = -16 + -33
-1x = -16 + -33

Combine like terms: -16 + -33 = -49
-1x = -49

Divide each side by '-1'.
x = 49

Simplifying
x = 49

See similar equations:

| 4x^2-19x+20=4x+5 | | 46-2x=8 | | 6x+6=122-10x | | 11x+3=4(3x+4) | | -x^5-x^3+4x=0 | | 11x+3=4x(3x+4) | | -49-7x=9x+17 | | D-8=12 | | 20=3w-1 | | 4k-9k=10j | | 12x(3x-3)-6x(7x-9)= | | 4(2x+3)=7x+4 | | B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x | | (x-6)(3x+4)=0 | | y=7+10x |

Equations solver categories